A Survey of Major Techniques of Clothing in Vision (Journal of Fiber Bioengineering and Informatics, 2015)
Clothing in vision plays an important role in many applications of digital clothing, virtual fitting, fashion\rdesign and manufacturing. The research of clothing in vision is full of technical challenges, such as\rbackground detection and features extraction. In this paper, we introduce the latest remarkable works\rof clothing in vision area, including clothing segmentation, clothing recognition and clothing retrieval.\rThere are many remarkable advances on the basis of the predecessors' achievements in the three fields.\rFirstly, we provide an overview of the techniques for clothing segmentation and clothing recognition.\rThen, we introduce and analyze the representative works on clothing retrieval. Finally, we forecast\rbroader application prospect and future research work of clothing in vision.